Theo-Monistic Mysticism - Stoeber, M. author. aut Link
X, 135 p.
Keywords: In response to some of the current explanations of mystic phenomena, this book proposes an interpretive framework for understanding mysticism. It clarifies various kinds of mystical experiences, suggesting they are not wholly determined by subjective categories of interpretation, and illustrates how they can be synthesised in a theistic, mystic teleology. In reference to Ramanuja, Aurobinodo, Sankara, Eckhart, Ruusbroec, and Boehme, monistic experiences are understood to culminate in higher theistic realizations, to which other kinds of mysticism can also be related.